Nepenthes mirabilis Fractionated Pitcher Fluid Use for Mixed Agro-Waste Pretreatment: Advocacy for Non-Chemical Use in Biorefineries - Angadam, J.O. (MDPI, 2022)
This study determined whether it is feasible to pretreat mixed agro-waste of different particle sizes using the pitcher fluid of Nepenthes mirabilis (N. mirabilis), which is known to digest leaf litter due to the enzyme cocktail contained in the fluid. This is due to the need for the holocellulol-ysis (a source of fermentable sugars) of mixed agro-waste to produce fermentable hydrolysates. The pitcher fluid was fractionated (<3 kDa, Ë3 kDa, <10 kDa, Ë10 kDa) and slurrified with the mixed agro-waste, i.e., 25 (w/w) for each wasteâorange peels, apple peels, maize cobs, grape pomace, and oak plant leaf litter of various particle sizes, i.e., >75 Âµm x < 106 Âµm and >106 Âµm. The process of producing a high concentration of total reducible sugars (TRSs) with the lowest production of total phenolic compounds (TPCs) was determined to be a particle size of >106 Âµm, pretreatment for 72 h, and an enzyme fraction of <10 kDa, whereby 97 g/L of TRSs were produced with a significantly lower TPCs load (1 g/L). Furthermore, the <10 kDa showed preferable physico-chemical properties, with the highest reduction-oxidation potential including acidity. Several enzymes, i.e., Î²-1,3-Glu-canase, Putative peroxidase 27, Thaumatin-like protein, among others, were identified in the <10 kDa fraction, i.e., enzymes known to perform various functions in plant-based waste. Therefore, there is a need for the renewable energy industry to consider solely using pitcher fluids to pretreat mixed agro-waste for fermentable hydrolysatesâ production, which can be used as liquid feedstock for the bioenergy and/or biorefinery industries for environmental pollution reduction. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.